Hemp Makassar: Pendirian, Hambatan dan Respon Masyarakat Terhadap Perjuangan Legalisasi Ganja Medis - PutriHasan, Salsabila Layla (Emik, 2024)
Cannabis which is still classified as a class one narcotic under law No. 35 of 2009 in Indonesia, has led to the formation of several organizations advocating for the legalization of cannabis, especially for medical purposes in Indonesia. This article deals with how Hemp Makassar struggle to advocate the legalization of cannabis for health in Indonesia. This qualitative research was conducted in the City of Makassar. The study involves ten informants which vary on the basis of sex (three women and seven men), age (between 21 and 38 years), position in Hemp (official staff and members of Hemp). Observation and in-depth interview are two types of data collection methods employed in this study. The study indicates that Hemp Makassar originated from a branch of LGN that splits off because they felt they were not given authority by the central LGN, as their methods of movement were considered deviant. Hemp's struggle is not just about speak out on the streets, but it also involves various methods and engages in different activities. On the way, Hemp faces various obstacles in its struggle to advocate the legalization of cannabis, namely misunderstandings, regulations and media involvement. The public's response to Hemp's struggle is divided into two: those who oppose and those who support the legalization of cannabis for health. Rejection towards the legalization of cannabis is often based on concerns about its social and health impacts, but those who support the legalization of cannabis are people who know and have experienced the positive benefits of cannabis.